Adiponectin as a biomarker linking obesity and adiposopathy to hematologic malignancies. - Dalamaga, Maria; Christodoulatos, Gerasimos S (Horm Mol Biol Clin Investig, 2015)
Higher body mass index and adiposopathy have been associated with increased risk of hematologic malignancies such as leukemia, multiple myeloma, myeloproliferative disorders, Hodgkin's and non-Hodgkin's lymphoma, and myelodysplastic syndromes. Adiponectin is a multimeric protein of the white adipose tissue presenting anti-inflammatory, insulin-sensitizing, anti-atherogenic, cardioprotective, and anti-neoplastic properties. Its anti-neoplastic actions are manifested via two mechanisms: (i) direct action on tumor cells by enhancing receptor-mediated signaling pathways and (ii) indirect action by regulating inflammatory responses, influencing cancer angiogenesis, and modulating insulin sensitivity at the target tissue site. In the bone marrow milieu, adiponectin and its main receptors are expressed by the majority of bone marrow stromal cell populations influencing hematopoietic stem cells function. Adiponectin may represent a molecular mediator relating adiposopathy with leukemogenesis and myelomagenesis. Several epidemiological studies conducted to date relate hypoadiponectinemia to the risk of myeloid-derived hematopoietic cancer and multiple myeloma. Adiponectin may be a promising biomarker with potential diagnostic and prognostic utility in determining the likelihood of myeloma and leukemia progression in certain cohorts of monoclonal gammopathy of undetermined significance patients and in myeloid hematologic malignancies, respectively. This review summarizes experimental and epidemiologic data regarding the role of adiponectin in hematologic malignancies in the context of adiposopathy. Enhancement of endogenous adiponectin, adiponectin replacement, or manipulation of adiponectin receptor sensitivity may be an attractive goal for prevention and an effective therapeutic strategy against hematopoietic cancer, specifically in overweight/obese individuals. Further studies are required to elucidate the role of the bone marrow microenvironment adiponectin in complex interactions involved in preleukemic and leukemic states.
Keywords: Adiponectin; Adiposity; Animals; Biomarkers; Body Mass Index; bone marrow; Hematologic Neoplasms; Humans; Obesity